Analysis on The ASEAN-PAC Contribution to The ASEAN Community Vision - Hermanto, Mikael Vidiananta; Sani, Muhammad Dzaky Putra; Ardiningrum, Paramesti Safa; Damaiyanti, Adrianita Putri (Journal of ASEAN Dynamics and Beyond, 2022)
Corruption has transcended beyond the geographical boundaries owing to globalization. Hence, states bearing the same concern regarding the atrocity of corruption created agreements and institutions with goals to combat corruption through mutual assistance. The countries in the southeast Asian region are no exceptions, most of which are member states of the ASEAN (Association of the Southeast Asian Nations). ASEAN members bear visions to participate in the fight against corruption, as encompassed in one of the three ASEAN Community Pillars: the ASEAN Political-Security Community (APSC). This paper is intended to research whether the making of ASEAN-PAC seems in line with and contributes to realize the ASEAN Community visions. Neoliberal Institutionalism is used to analyze how beneficial is the making of ASEAN-PAC for the continuity of the ASEAN Community ― also whether it’s stable or not― and its members. For the research method, this paper used a qualitative approach, namely literature reviews. It utilizes a simple but thorough reading on any journal articles or books. The results shows that the ASEAN mutual consensus to combat corruption was then improved in the ASEAN Parties Against Corruption (ASEAN-PAC), which was established so as to strengthen the bond among ASEAN members as well as accommodating Mutual Legal Assistance (MLA) in tackling transnational corruption. Nevertheless, there has yet to be a solid framework from ASEAN PAC to acquire the noble vision. Apart from this delay, the ASEAN Community seems to be observing the EU as an institutional role model with what efforts it made to follow in the latter’s footsteps.